Molecular analysis of RNA polymerase alpha subunit gene from Streptomyces coelicolor A3(2). - Cho, E J (1996)
The rpoA gene, encoding the alpha subunit of RNA polymerase, was cloned from Streptomyces coelicolor A3(2). It is preceded by rpsK and followed by rplQ, encoding ribosomal proteins S11 and L17, respectively, similar to the gene order in Bacillus subtilis. The rpoA gene specifies a protein of 339 amino acids with deduced molecular mass of 36,510 Da, exhibiting 64.3 and 70.7% similarity over its entire length to Escherichia coli and B. subtilis alpha subunits, respectively. Using T7 expression system, we overexpressed the S. coelicolor alpha protein in E. coli. A small fraction of this protein was found to be assembled into E. coli RNA polymerase. Antibody against S. coelicolor alpha protein crossreacted with that of B. subtilis more than with the E. coli alpha subunit. The ability of recombinant alpha protein to assemble beta and beta' subunits into core enzyme in vitro was examined by measuring the core enzyme activity. Maximal reconstitution was obtained at alpha2:beta+beta' ratio of 1:2.3, indicating that the recombinant alpha protein is fully functional for subunit assembly. Similar results were also obtained for natural alpha protein. Limited proteolysis with endoproteinase Glu-C revealed that S. coelicolor alpha contains a tightly folded N-terminal domain and the C-terminal region is more protease-sensitive than that of E. coli alpha.